Teachers’ Experiences and Views on the School Education of Children from Roma Communities: Empirical Research in Central and Western Macedonia - Καλογερογιάννη Φωτεινή; Χατζηδήμου Κωνσταντίνος (Education Sciences, 2025)
This study aims to contribute to the ongoing discourse on the professional development of teachers at all educational levels in relation to the acquisition of intercultural competence. Data were collected through an open-ended written response, in which participants were invited to share their views and experiences. The participants in the study were teachers who attended the training activities of the program “Supportive interventions in Roma communities to enhance access to and reduce school dropout among children and adolescents in Central and Western Macedonia” (2020–2023) during the 2022–2023 school year. A total of 32 teachers from all educational levels participated in the study. The method of content analysis was applied to the data, combining both quantitative and qualitative approaches. The findings highlight teachers’ attitudes toward critical issues such as the schooling of children from Roma communities, the relationship between family and school, the role of the school community, and the causes of school dropout. At the same time, the study presents ways to improve the educational situation, as proposed by the teachers themselves based on their experiences with students from Roma communities.